A correlational gender study on I.Q. and emotional maturity quotient among college students - Napari, Odhella Corazon L. (Tacloban City Odhella Corazon L. Napari, 1999)
Man's effective adjustment with his environment is a function of his intelligence and ability to control his emotions, strife for survival, and his ability to be bonded and maintain good social relationships. This study is concerned with the relatedness of I.Q. and Emotional Maturity Quotient through correlation of scores and tests whether there are significant differences in the I.Q. levels and emotionality of men and women.
According to Daniel Goleman in his book entitled the Emotional Intelligence, I.Q. and Emotional Intelligence are only slightly correlated. Since no universally recognized test of Emotional Intelligence is yet found, the researcher prompted the use of an Emotional Maturity Quotient Test and I.Q. scores to test Goleman's contention. In trying to prove its validity, the researcher presents the following hypotheses: (1) I.Q. is highly correlated with high Emotional Maturity Quotient, (2) There is no significant difference in the I.Q. levels of men and women, (3) There is a significant difference related to the emotionality of men and women.
The researcher used 40 respondents, with 20 males and females who were Freshmen College students at the University of the Philippines SY 1998-1999. They were selected through systematic random sampling method. An emotional maturity quotient test entitled, "Are you grown up?" was presented to them, and their scores were obtained from the Office of UPVTC Student Affairs, in the Guidance and counseling section. In statistical treatment, the researcher used Pearson's Correlation Coefficient using two formula, the raw score and standard formula. Two t-tests were likewise applied to test the second and third hypothesis.
The results of the statistical treatment using two Pearson's Correlation Coefficient formula revealed that I.Q. and Emotional Maturity Quotient are lowly correlated with an R= 0.26. There is also no significant difference in the I.Q. levels of men and women since the value of t= -0.80 at 0.5 level of significance. There is, indeed, a significant difference in the emotional maturity of men and women with a value of t= 2.75 because it is greater than the tabular value equal to 2.021 at 0.5 level of significance.
Keywords: Emotional Maturity Quotient (EMQ).; I.Q.; Social Science